1988
DOI: 10.1177/154193128803201904
|View full text |Cite
|
Sign up to set email alerts
|

A Signal Detection Paradigm for Color Display Specification

Abstract: The objective of this research was to demonstrate the validity of signal detection theory to the assessment (visual discrimination) of displayed color symbology. The area of application of the research results is in the design specification of color coded symbology to be overlayed on moving map, situational awareness displays. A symbol detection experiment was designed to determine how far apart, in CIE/UCS color space, symbol and background color must be in order for observers to detect that a symbol is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
1991
1991

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Previous research (Wilson, Kuperman, Ramsey, and Perez, 1988) has demonstrated the validity of signal detection theory to the visual discrimination of displayed color symbology. This theory incorporates into a single model the many disparate factors that affect the detection and recognition of signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research (Wilson, Kuperman, Ramsey, and Perez, 1988) has demonstrated the validity of signal detection theory to the visual discrimination of displayed color symbology. This theory incorporates into a single model the many disparate factors that affect the detection and recognition of signals.…”
Section: Introductionmentioning
confidence: 99%
“…In their description of operator interface for future bomber crewstations, Kuperman and Wilson (1988) posit a Tactical Situation Display which employs color graphics with a moving map underlay. One of the functions of the moving map underlay is to convey terrain elevation information, it might be expected that a number of colors would be needed to code the elevations.…”
Section: Introductionmentioning
confidence: 99%